2020
DOI: 10.3174/ajnr.a6392
|View full text |Cite
|
Sign up to set email alerts
|

MR Diffusional Kurtosis Imaging–Based Assessment of Brain Microstructural Changes in Patients with Moyamoya Disease before and after Revascularization

Abstract: BACKGROUND AND PURPOSE: Conventional imaging examinations are insufficient to accurately assess brain damage in patients with Moyamoya disease. Our aim was to observe brain microstructural changes in patients with Moyamoya disease by diffusional kurtosis imaging and provide support data for application of this technique in individualized assessment of disease severity and surgical outcome among patients with Moyamoya disease. MATERIALS AND METHODS: A total of 64 patients with Moyamoya disease and 15 healthy vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…In this study, evaluating patients with MMD treated with revascularization surgery and normal controls, parametric changes before surgery were most frequently observed in the parameters representing extracellular free water rather than free water-eliminated neuronal parameters. These results suggest that altered parenchymal free water may largely contribute to alterations in conventional diffusion parameters rather than the change in neurites in patients with MMD, as well as other neurological diseases [4,8,7]. This result is consistent with a previous study using NODDI and showed increased extracellular free water (V iso ) in patients with MMD [14].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, evaluating patients with MMD treated with revascularization surgery and normal controls, parametric changes before surgery were most frequently observed in the parameters representing extracellular free water rather than free water-eliminated neuronal parameters. These results suggest that altered parenchymal free water may largely contribute to alterations in conventional diffusion parameters rather than the change in neurites in patients with MMD, as well as other neurological diseases [4,8,7]. This result is consistent with a previous study using NODDI and showed increased extracellular free water (V iso ) in patients with MMD [14].…”
Section: Discussionsupporting
confidence: 90%
“…We found no direct relationship between postoperative changes in conventional FA and postoperative cognitive improvement, as in previous studies [8,4,7], and found no direct relationship between the postoperative reduction in free water and cognitive improvement. It is reasonable to assume that the postoperative cognitive improvement resulting from neuronal alterations causes functional and metabolic improvement [36,8,22] and that cognition is unrelated to the amount of extracellular free water [14].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This is because the GM microstructure lacks evident directionality that the radial and axial directions will be random and highly influenced by noise (21). However, a variety of changed Kr, Dr, Ka, and Kr in GM continue to be reported in normal aging (9)(10)(11)(12)22), in Moyamoya Disease (23), in Bipolar Disorders (24), and in various neurodegenerative processes including Alzheimer's disease (25,26) and Parkinson's disease (27,28). In fact, some of the deep GMs are composed of both gray matter and white matter (10,29).…”
Section: Diffusion and Kurtosis Parametersmentioning
confidence: 99%
“…Because there is a tendency for multiple structural T1 acquisitions to produce similar contrast between GM and WM (these tissues have a common appearance across T1 pulse sequences), it was hypothesized that regional relative signal intensities (RRSIs), which focus on the ratio of the WM signal intensity (SI) to the GM SI, may provide a degree of standardization for the comparison of SI‐based biomarkers across pulse sequences. We hypothesize that thorough assessment of a large clinical population of MRI examinations will contribute to the body of data acquired on paediatric MMD and thus improve our collective understanding of the clinical presentation of the condition, which has been shown to exhibit regional abnormal growth in both the WM and GM (Kazumata et al, 2015; Qiao et al, 2020). We also hypothesize that RRVs and RRSIs may help better characterize the changes in the brains of patients with MMD and may represent biomarkers with the potential to assist in the assessment and characterization of brain development while potentially playing a role in overcoming varying protocol standardization challenges from clinical MRI examinations.…”
Section: Introductionmentioning
confidence: 99%